Time Management Among Future Workforce: Mobile Technology, Digital Literacy, and Self-Directed Learning - Venezia Thalia Metekohy; Fredy Hendry Louhenapessy; Ryalno Stefano Noya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid digital transformation of the workplace has increased the demand for competencies that extend beyond technological proficiency. As prospective members of the future workforce, university students are expected to effectively manage their time, utilize digital information, and engage in self-directed learning. This study examines the effects of mobile technology, digital literacy, and self-directed learning on students’ time management. A quantitative survey design was employed involving 150 students from the Fakultas Ekonomi dan Bisnis at Pattimura University, selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that digital literacy has a positive and significant effect on students’ time management. Self-directed learning also shows a significant influence, although the relationship is negative. In contrast, mobile technology does not significantly affect time management. These findings suggest that effective time management is influenced more by students’ ability to process digital information and regulate their learning than by technology usage alone. The novelty of this study lies in integrating mobile technology, digital literacy, and self-directed learning into a single framework to explain time management among students as future workforce candidates. The findings provide practical implications for higher education institutions in strengthening digital competencies and self-management skills.